The Impact of Nurses' Disaster Preparedness Competencies on Public Health Center Resilience in Disaster-Prone Areas: A cross-sectional study - Moh Ikram Dg Sirua; Balqis Balqis; Muhammad Alwy Arifin; Indar Indar; Syamsuar Manyullei (Asia Pacific Journal of Health Management)
Background: Disaster-prone areas need resilient health centers to ensure effective health management services and emergency response during earthquakes and tsunamis. Nurses play a critical role in disaster risk reduction which is essential to improving health center resilience. Resilience includes the ability of health centers to withstand, adapt to, and recover from the effects of disasters while continuing to provide essential health services. This study examined the influence of nurses' disaster preparedness skills on health center resilience in disaster scenarios.